2006
DOI: 10.1128/jvi.01149-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus F9 Virion Membrane Protein Is Required for Entry but Not Virus Assembly, in Contrast to the Related L1 Protein

Abstract: All sequenced poxviruses encode orthologs of the vaccinia virus L1 and F9 proteins, which are structurally similar and share about 20% amino acid identity. We found that F9 further resembles L1 as both proteins are membrane components of the mature virion with similar topologies and induce neutralizing antibodies. In addition, a recombinant vaccinia virus that inducibly expresses F9, like a previously described L1 mutant, had a conditional-lethal phenotype: plaque formation and replication of infectious virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
0
60
0
Order By: Relevance
“…A distinction between the integral components of the EFC and the so-called "EFC-associated" proteins is the exclusive role of the former in the assembly or stability of the complex (3,4,39). To determine the effect of repressing O3 expression, the A28R ORF in vO3-HAi was replaced with a copy containing tandem-affinity calmodulin and streptavidin binding peptide tags to form vO3-HAi-A28TAP.…”
Section: Resultsmentioning
confidence: 99%
“…A distinction between the integral components of the EFC and the so-called "EFC-associated" proteins is the exclusive role of the former in the assembly or stability of the complex (3,4,39). To determine the effect of repressing O3 expression, the A28R ORF in vO3-HAi was replaced with a copy containing tandem-affinity calmodulin and streptavidin binding peptide tags to form vO3-HAi-A28TAP.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are conserved in all poxviruses, which suggests that their functions are nonredundant and essential. Recently, coimmunoprecipitation studies confirmed that F9 and L1, which are also required for cell entry and membrane fusion, interact with the EFC (13,18). The poxvirus regulatory fusion proteins A56 and K2 have been shown to form a complex in the EV and at the cell surface by immunoprecipitation (166) ( Table 4).…”
Section: Virus-virus Protein Interactionsmentioning
confidence: 98%
“…Of these proteins, A17L, A26L, and L1R are established membrane proteins, as are E8R (39) and F9L (40). G9R is presumed to be membrane associated, as a myristoylated member of the poxvirus entry-fusion complex (41).…”
Section: Fig 2 Confidently Identified Vaccinia Virus and Host Proteinmentioning
confidence: 99%